Optimization of Metallic Catalytic Converters to Reduce CO Emissions and Increase Engine Power - Warju Warju; Sudirman Rizki Ariyanto; Muhammad Yandi Pratama; Kusuma Refa Haratama (Automotive Experiences, 2024)
Metallic catalytic converter (MCC) is one of the technologies widely applied to motorcycle exhausts which aims to improve exhaust emission to be more environmentally friendly. However, even though many studies have been conducted, optimal design has not been achieved compared to other designs. Through this research, the Taguchi method is proposed as an alternative method to find the optimum parameters of MCC. The Taguchi method was chosen because of its ability to find a robust combination of parameters. There are four MCC parameters used as inputs while each parameter consists of three levels, thus the design used is the L18 Orthogonal Array (OA) which each combination is tested on three types of motorcycles, namely Moped, Automatic, and Sports. The signal-to-noise ratio (S/N) was adopted as one of the quality indicators of each combination. The optimization results showed that the best MCC design to reduce CO emissions is STD PGM. However, the optimum CO design can be used as an alternative because the difference in the S/N ratio is only -0.372. Meanwhile, the optimum CO design has another advantage over the STD PGM, namely the S/N value of the power ratio which tends to be higher with a difference of 5.037 compared to the STD PGM. Then, the best MCC design capable of increasing power is the optimum power design. The optimum power design has a superior S/N ratio with a difference of 5.404. In terms of emission, the optimum power design tends to be lower by a difference of -1.875 compared to the STD PGM.